2018
DOI: 10.1016/j.jfludis.2017.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous network architecture of the resting brain in children who stutter

Abstract: This study supports the view that stuttering is a complex neurodevelopmental disorder and provides comprehensive brain network maps that substantiate past theories emphasizing the importance of considering situational, emotional, attentional and linguistic factors in explaining the basis for stuttering onset, persistence, and recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
35
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 174 publications
(201 reference statements)
4
35
0
10
Order By: Relevance
“…These were chosen to interrogate major brain cell types and brain areas previously suggested to be sites of the primary neurological deficit in stuttering. Our first hypothesis was chosen based on imaging studies of the brains of humans who stutter, which have detected associations between stuttering and white matter deficits, including altered connectivity (10,28,29). White matter contains no neuronal cell bodies or synapses but does contain tightly packed glial cells, including oligodendrocytes (which produce myelin), astrocytes, and microglia.…”
Section: Neuropathology Studies and Reduced Astrocyte Staining Densitmentioning
confidence: 99%
See 1 more Smart Citation
“…These were chosen to interrogate major brain cell types and brain areas previously suggested to be sites of the primary neurological deficit in stuttering. Our first hypothesis was chosen based on imaging studies of the brains of humans who stutter, which have detected associations between stuttering and white matter deficits, including altered connectivity (10,28,29). White matter contains no neuronal cell bodies or synapses but does contain tightly packed glial cells, including oligodendrocytes (which produce myelin), astrocytes, and microglia.…”
Section: Neuropathology Studies and Reduced Astrocyte Staining Densitmentioning
confidence: 99%
“…A primary goal for stuttering research has been to understand the neuropathology underlying this disorder. Imaging studies have identified differences in the brains of individuals who stutter (7)(8)(9)(10). However, such studies have been limited by the difficulty of determining whether these differences are the cause of stuttering or the result of stuttering, and by the fact that they do not provide resolution at the cellular and molecular level.…”
mentioning
confidence: 99%
“…The pathophysiology of stuttering is still unclear. There is, however, increasing evidence of subtle structural and functional differences in the brains of adults and children who stutter relative to their fluent peers [Beal et al, 2013;Chang et al, 2015Chang et al, , 2017Chang and Zhu, 2013;Connally et al, 2014;Cykowski et al, 2010;Desai et al, 2017;O'Neill et al, 2017;Watkins et al, 2008]. One line of research investigated the property of white matter microstructure by measuring fractional anisotropy (FA), which reflects white matter coherence or integrity, through diffusion tensor imaging (DTI).…”
Section: Introductionmentioning
confidence: 99%
“…Niet onbelangrijk om te benoemen in dit verband is een zeer recente en omvangrijke hersenstudie naar 84 jonge kinderen die de gedachtegang van bredere en mogelijk niet-spraak gerelateerde oorzaken van stotteren bevestigt (Chang et al, 2017). In deze studie werd met behulp van fMRI de connectiviteit tussen neurale netwerken van het brein geanalyseerd tijdens rusttoestand.…”
Section: Experimenteel Bewijs Voor Afwijkende Monitoring In Stotterenunclassified